Nanomedicine applications in orthopedic medicine: state of the art - Mazaheri M (Dove Medical Press, 2015)
Mozhdeh Mazaheri,1,* Niloofar Eslahi,1,* Farideh Ordikhani,1,* Elnaz Tamjid,2 Abdolreza Simchi1,3 1Department of Materials Science and Engineering, Sharif University of Technology, 2Department of Nanobiotechnology, Faculty of Biological Sciences, Tarbiat Modares University, 3Institute for Nanoscience and Nanotechnology, Sharif University of Technology, Tehran, Iran *These authors contributed equally to this work Abstract: The technological and clinical need for orthopedic replacement materials has led to significant advances in the field of nanomedicine, which embraces the breadth of nanotechnology from pharmacological agents and surface modification through to regulation and toxicology. A variety of nanostructures with unique chemical, physical, and biological properties have been engineered to improve the functionality and reliability of implantable medical devices. However, mimicking living bone tissue is still a challenge. The scope of this review is to highlight the most recent accomplishments and trends in designing nanomaterials and their applications in orthopedics with an outline on future directions and challenges. Keywords: orthopedics, nanomedicine, tissue engineering, implantable materials, nanotoxicology